Fenomena Media Sosial Berkonten Seks Terhadap Implikasi Perkawinan Dini di Kecamatan Luyo Kabupaten Polewali Mandar - Farham Rahmat; Marilang; Subehan Khalik (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study is a type of qualitative research that aims to determine the intensity of the use of social media with sex content among early childhood and the significance of its influence on early marriage in Luyo District Polewali Mandar Regency. Data obtained from in-depth interviews with 25 respondents as perpetrators of early marriage and 10 supporting respondents and processed using Miles and Huberman Model Analysis. The results of this study stated that the intensity of social media use with sex content among minors in Luyo Sub-District, Polewali Mandar Regency, reached 3-4 hours/day. classified as moderate when compared to APJII data that reaches 5-6 hours/day in terms of the use of social media platforms, the significance of the influence of social media, based on research found the perspective of 19 informants from 25 interviewed said social media had quite an effect on early marriage decisions, sex content had an effect to arouse adolescent sexual arousal, so that social Media with sex content in Luyo District, Polewali Mandar Regency is said to have a significant influence on some informants in conducting early marriage practices. The implication of this study is that it can be a basis for educators, parents, and governments to understand the impact of social media on sexual content, can be a consideration for policy makers in formulating regulations that limit or regulate children and adolescents ' access to social media with sexual content and help communities and families to be more vigilant and control the use of social media by children and adolescents at home. For further researchers who are interested in researching a similar topic so that presumably before conducting research, it is necessary to first conduct a survey to clarify the data of the respondents to be studied and more detailed statements or questions used to make it easier to understand